2020
DOI: 10.3390/ijerph18010250
|View full text |Cite
|
Sign up to set email alerts
|

Global Burden of Headache Disorders in Children and Adolescents 2007–2017

Abstract: Headache disorders are prevalent and disabling conditions impacting on people of all ages, including children and adolescents with substantial impact on their school activities and leisure time. Our study aims to report specific information on headaches in children and adolescents based on the Global Burden of Disease (GBD) study, that provides estimates for incidence, prevalence, fatal and non-fatal outcomes. We relied on 2007 and 2017 GBD estimates for prevalence and Years Lived with Disability (YLDs) at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 31 publications
0
37
0
2
Order By: Relevance
“…Our study represents one of the few studies that consider nonpharmacological therapies in adolescents with CM or HFEM, showing some feasibility in using these methods as part of the treatment in this patient population. As other studies have previously suggested, behavioral and mindfulness-based approaches can be of great support in reducing pain and disability in young patients [12,[18][19][20][21], and represent a valid alternative to pharmacological prophylaxis which show little or no superiority to placebo [15][16][17]. The psychological aspects involved in the burden of headache in adolescents include different areas of life, not only of the patient themselves but also of the family members, so multidisciplinary care is necessary to improve the quality of life of all those involved [12].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our study represents one of the few studies that consider nonpharmacological therapies in adolescents with CM or HFEM, showing some feasibility in using these methods as part of the treatment in this patient population. As other studies have previously suggested, behavioral and mindfulness-based approaches can be of great support in reducing pain and disability in young patients [12,[18][19][20][21], and represent a valid alternative to pharmacological prophylaxis which show little or no superiority to placebo [15][16][17]. The psychological aspects involved in the burden of headache in adolescents include different areas of life, not only of the patient themselves but also of the family members, so multidisciplinary care is necessary to improve the quality of life of all those involved [12].…”
Section: Discussionmentioning
confidence: 81%
“…CM and HFEM impact patients' emotional, social, and school functioning [8][9][10][11]. A recent report showed that structured and tailored public health policies and strategies, including diagnosis, pharmacological and nonpharmacological treatments helped to reduce burden and disability [12]. In adolescent patients, the inclusion of nonpharmacological approaches, such as nutraceuticals or behavioral techniques [13,14] as a support for traditional pharmacological therapies were suggested.…”
Section: Introductionmentioning
confidence: 99%
“…For many years now, migraine has been positioned among the first places in the unenviable ranking of disability 8,9 , not only in adults but also in adolescents 10 , and the awareness of its importance as a social disease has now been established. Numerous studies on very large patient populations have shown in different geographical areas how the burden of migraine affects these patients widely at all latitudes when evaluated in terms of Health-Related Quality of Life, work productivity, healthcare resource utilization, cost of illness [11][12][13][14][15] .…”
Section: Burden Of Migraine Worldwidementioning
confidence: 99%
“…Migraine is a primary headache disorder defined as a prevalent neurologic disease characterized by headaches that can occur with or without aura, consisting of transient focal neurological symptoms (visual, sensory, speech and/or language, motor, brainstem and retinal) that usually precede by hours or days, or sometimes accompany, the headache [ 1 ]. The social worldwide burden of migraine is noteworthy since it ranks the sixth most prevalent disease and the second cause of disability worldwide [ 2 ], accounting for around 7 % of all-cause Years Lived with Disability (YLD) and for 72 % of all YLDs associated to neurological disorders [ 3 ]. In fact, according to report from the Global Burden of Disease Headache in 2018, 14.4 % of the global population suffers from migraine making of it the global second leading cause of disability [ 4 ].…”
Section: Introductionmentioning
confidence: 99%